Micro-Lightguide Spectrophotometry (O2C) for Lower Limb Perfusion: Effects of Exercise Walking in Claudicants - Gyldenløve, Thomas; Jørgensen, Lise P.; Schroeder, Torben V. (International Journal of Angiology, 2019)
Background Exercise walking has improved walking capacity in patients with intermittent claudication without affecting the macrocirculation reflected in ankle pressures. We wanted to investigate microcirculation in the skin related to exercise walking by using Micro-Lightguide Spectrophotometry (O2C).Materials and Methods Twenty-eight patients with intermittent claudication—bilateral in 17—were included in a 12 weeks of structured home-based exercise program. The pain-free and maximal walking distances were determined on a treadmill. Saturation and flow, monitored by O2C, were examined immediately before and after the treadmill test. O2C examination took place before as well as after completion of the exercise program. Ankle–brachial index was obtained before treadmill testing.Results As expected, walking performance improved significantly without affecting ankle pressures. Neither oxygen saturation nor flow, assessed at 2 mm depth, was affected following a 12 weeks of exercise program. We observed a significant decrease in oxygen saturation and flow upon treadmill testing in the both limbs in patients with bilateral peripheral arterial disease (PAD). In contrast, the treadmill test elicited no changes in the opposite and asymptomatic limb in patients with only unilateral PAD.Conclusion The findings suggest that O2C may be used to study microcirculatory changes. However, it is best suited for the study of phenomena resulting in major changes as it eliminates some inherent variability.
Keywords: claudication; atherosclerosis; ischemia; lower extremity; peripheral artery disease